Using PQ4R to Improve Students’ Reading at Emergency Remote Learning - Nia Zupita; Yayah Nurhidayah; Eka Nurhidyat (ITScience (Information Technology and Science), 2021)
Emergency remote learning is a substitute for face-to-face teaching and learning activities during the COVID-19 pandemic. Students feel various problems in the teaching and learning process, especially reading English text in this study. Students feel uncomfortable, less handling, reading text must be repeated to understand, and the more wanted problems in this study are the mean score of reading students is still lacking. There is no particular method used in reading. Therefore, this study proposed the PQ4R method as a method that could be used to improved students' homework. This research was qualitative and quantitative with the CAR (Classroom Action Research) method, and the data collection techniques were tests and questionnaires. This study also used triangulation as data validation. The mean score of students ' reading has increased from the existing situation, the first cycle, to the second cycle. The current situation means the score was 65.16, the mean score of the first cycle was 78.03, and the mean score of the second cycle was 88.94. In addition, students' responses to the PQ4R method were positive. The results of this study indicated that the PQ4R process could improve students' reading mean scores.